Advances in 3D printing & additive manufacturing technologies - Wimpenny, D. I.; Pandey, Pulak M.; Kumar, L. Jyothish (Springer, 2016)
"This edited volume comprises select chapters on advanced technologies for 3D printing and additive manufacturing and how these technologies have changed the face of direct, digital technologies for rapid production of models, prototypes and patterns. Because of its wide applications, 3D printing and additive manufacturing technology has become a powerful new industrial revolution in the field of manufacturing. The evolution of 3D printing and additive manufacturing technologies has changed design, engineering and manufacturing processes across industries such as consumer products, aerospace, medical devices and automotives. The objective of this book is to help designers, R & D personnel, and practicing engineers understand the state-of-the-art developments in the field of 3D Printing and Additive Manufacturing."-- Back cover.
Keywords: Additive manufacturing.; Three-dimensional printing.; Rapid prototyping.; Solid freeform fabrication.; elektronické knihy; electronic books